Can the general theory of crime and general strain theory explain cyberbullying perpetration? - Lianos, Helen (Crime & delinquency, 2018)
Cyberbullying is an increasingly common characteristic of contemporary online communication. The current study surveyed 320 Internet-active young adults and found up to 80% reported engaging in this behavior at least once. In addition, the ability of the general theory of crime and general strain theory to explain cyberbullying perpetration was tested. Evidence for both theories was observed, with both low self-control and higher levels of strain related to cyberbullying perpetration. Furthermore, opportunity (operationalized as moderate and high number of hours online) interacted with low self-control to increase perpetration, and anger partially mediated the relationship between strain and cyberbullying. Implications of the findings are discussed.